Phytochemical Analysis and Biological Activities of Cola nitida Bark. (12th February 2015) - Dah-Nouvlessounon, Durand; Adoukonou-Sagbadja, Hubert; Diarrassouba, Nafan; Sina, Haziz; Adjanohoun, Adolphe; Inoussa, Mariam; Akakpo, Donald; Gbenou, Joachim D.; Kotchoni, Simeon O.; Dicko, Mamoudou H.; Baba-Moussa, Lamine
Abstract : Kola nut is chewed in many West African cultures and is used ceremonially. The aim of this study is to investigate some biological effects of Cola nitida 's bark after phytochemical screening. The bark was collected, dried, and then powdered for the phytochemical screening and extractions. Ethanol and ethyl acetate extracts of C. nitida were used in this study. The antibacterial activity was tested on ten reference strains and 28 meat isolated Staphylococcus strains by disc diffusion method. The antifungal activity of three fungal strains was determined on the Potato-Dextrose Agar medium mixed with the appropriate extract. The antioxidant activity was determined by DPPH and ABTS methods. Our data revealed the presence of various potent phytochemicals. For the reference and meat isolated strains, the inhibitory diameter zone was from17.5 ± 0.7  mm ( C. albicans ) to9.5 ± 0.7  mm ( P. vulgaris ). The MIC ranged from 0.312 mg/mL to 5.000 mg/mL and the MBC from 0.625 mg/mL to >20 mg/mL. The highest antifungal activity was observed with F. verticillioides and the lowest one with P. citrinum . The two extracts have an excellent reducing free radical activity. The killing effect of A. salina larvae was perceptible at 1.04 mg/mL. The purified extracts of Cola nitida 's bark can be used to hold meat products and also like phytomedicine.